A Comprehensive Assessment of Water Poverty in Mahendragarh District of Haryana - Thakur, Swati; Inder Jeet (National Geographical Journal of India, 2022)
Measures of water availability and socio-economic capacity to access to it comprehensively can be significant to water resource management and poverty alleviation. However, research about selection of areas of greatest need to prioritize management action is scarce at local scale. The purpose of this paper is to demonstrate the application of WPI (Water Poverty Index) to map magnitude of water scarcity and identify water poor in the Mahendragarh district of Haryana. The area is characterized by low rainfall (421mm annual average), devoid of Perennial River System and depleting ground water. The economic growth rate of the district (7.3) stands far less than state average (8.8) reflecting the socio-economic status of the population. Both primary data and secondary sources like, CGWB (Central Ground Water Board), Chandigarh, Agriculture and Irrigation Department, Panckula and IMD, Pune has been used to assess water poverty. Based on benchmark approach to calculate scores of five components, ’Resource’, ’Access’, ’Capacity’, ’Use’ and ’Environment’, the value of WPI is calculated using additive aggregation method, assuming equal weights for all components. The overall WPI score evaluated is 38.62, depicting severe water poverty with Zerpur (25.25) and Ateli Mandi (49.08) having worst and the best conditions among all villages. Access and Capacity were found to be significantly correlated with WPI implying that any attempt to improve water poverty must first tackle these. WPI was found to be an effective indicator to make priority areas for water management.